Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

what is the intercept form ?
ax^2+bx+c = standard form
y=a(x-h)^2+k vertex form

x=-2 , x=3
set it equal to zero

okay... then do I plug in something?

then you would apply foil method to get the standard form

foil method? o.o//

(a+b)(c+d) multiply ? FOIL familiar with it ?

-2^2 +3+-4=

??? cross multiply, sorry I don't really remember...

...

y=(x^2+x^3)^4 ???

a)^^

given x-intercepts are -2 and 3
so substitute p and q for -2 and 3

I never really learned this, so don't be mad... Anyways okay

i've never heard abt intercept form
this is first time i'm doing this

feel free to ask question if you don't get anything :)

a= - y/2x(x-3)

a=−y2x(x−3)

okay :/

@Robert136 please help?

replace y with -4

read the statement of the original question

a=-4/2x(x-3)

\[\huge\rm -4=a(\color{reD}{0}-(-2))(\color{reD}{0}-3)\]
like this now solve for a

a=2/3

yes right so intercept for would be ?
\[\huge\rm y=a(x-p)(x-q)\]
replace a with 2/3
p =-2
q=-3

y= 1/2 (x --2) (x--3)?

a =2/3 not 1/2

opps xD i don't know where that came from xD

\[\huge\rm y=\frac{ 2 }{ 3 }(x\color{reD}{-(-2)})(x-3)\]
distribute -(-2)

y=2/3(x--2)(x--3)

hmm q isn't -3

\[\huge\rm y=\frac{ 2 }{ 3 }(x\color{reD}{-(-2)})(x-(+3))\]
distribute -(-2)

-1 times -2 = ?
- times +3 = ?

-2?
3

after that you wll with part a

negative times negative = positive

so -1 times -2 = ?

yes so
-1 times 3 = ?

-3?

right

okay xD

2, -3

\[\huge\rm y=\frac{ 2 }{ 3 }(x+2))(x-3)\]

y=2/3(x+2)(x-3)

lol

yep!

xD ♥

now multiply 2/3(x+2)(x-3)
and i've to go now sorry
its urgent :(

cya

sorry I had to go the restroom...

are you there ?

tag me when u're ready okay :)

hey

still here sups, aha

okay great ready !?

`Write in ax2 + bx + c form. `
multiply 2/2(x-3)(x+2)

okay hold up

x^2-x-6?

(x+2)(x-3)=x^2-x-6 now multiply it by 2/3

okay

let me know what u get

I get nothing :/

what do you mean ?

I get 0

also sorry I had to leave the computer
:/

how did you get 0 ??
2/3(x-3)(x+2) ??

multiplied....

2x^2/3 - 2x/3 -4???